Air-sea interactions over the Gulf Stream region : benefits of higher-resolution in the representation of the physical mechanisms and climate impacts - Rousseau, Victor (HAL CCSD, 2020)
This thesis aims at understanding the role of sea surface temperature (SST) fronts on air-sea interactions in the Gulf Stream region. We study the local response of the atmosphere to the SST mesoscale variability, not only within the marine atmospheric boundary layer (MABL), but also in the free troposphere. We also evaluate the impact of SST fronts beyond the Gulf Stream region, in particular on the North Atlantic atmospheric circulation and climate over Europe. We focus on the winter season (December-January-February), when air-sea contrasts and hence air-sea exchanges are the strongest. On this purpose, we perform and analyze numerical experiments, using the global atmospheric model ARPEGEv6 forced by observed daily SSTs at high resolution (1/4°). In the first part of this thesis we investigate two major MABL mechanisms responsible for the atmospheric response to the SST fronts over the Gulf Stream region. These mechanisms are the vertical mixing and the pressure adjustment mechanisms. Two sets of atmospheric simulations performed with two ARPEGEv6 configurations are considered: a low-resolution version (140 km) and a high resolution version (50 km). We analyze the response of the divergence of the near surface wind, because this is one of the main imprint of the MABL response to the SST front. While in most of previous studies monthly averages were used to study the response of the wind divergence to the SST fronts, our results highlight the key role of synoptic atmospheric perturbations on modulating the contribution of these two MABL mechanisms and hence on shaping the time-mean divergence of near surface wind. We show in particular that most of the winter-mean wind divergence simulated above the Gulf Stream region can be explained by the cyclonic anomalous circulation that occurs during extreme conditions of heat flux exchanges. The comparison of the results obtained with the high and low resolution versions of the atmospheric model shows that the impact of model resolution is small compared to internal ...